Strategy in Anticipating the Hospital’s Financial Condition During the Covid-19 Pandemic (Syntax Corporation Indonesia, 2021)
The registration section is the front line of health service activities in health care facilities. There are many obstacles that occur in the registration section for various reasons. The limited workforce in the registration section is one of the causes of these obstacles. This study aims to analyze how many workforces needed in the medical record unit at the registration section of the Tanjungsari Medika Clinic based on the workload. This research is a descriptive research with observation and interview data collection methods. This study also uses the WISN (Workload Indicators Staffing Needs) method. WISN is a method used to calculate labor requirements based on workload. The data sample in this study was the number of patient visits at the Tanjungsari Medika Clinic for the period of July 2020 - June 2021, which amounted to 21619 outpatient visits and 3332 observation patient visits. From the results of the calculations in this study, it can be concluded that it is necessary to add 1 more person in the medical record unit at the Tanjungsari Medika Clinic in order to achieve quality health services with a qualified workforce as well.